Substitutes for Leadership: Test of a Construct - Howell, Jon P.; Dorfman, Peter W. (Academy of Management Journal, 1981)
The study reported here examined the impact of leadership substitutes on subordinate job satisfaction and organizational commitment. Leadership substitutes, as suggested by Kerr (1977), replace or ?act in the place of? a specific leader behavior. Multiple regression was used to test the validity and strength of potential substitutes. Results indicated mixed support for the substitutes construct.